Calvino's Reality: Designer's Utopia. - Jacob, Johanna (Utopian Studies, 1998)
Addresses a utopian approach to teaching and learning graphic design for the future. Context of graphic design; Focus of graphic design education; Concepts offered by author Italo Calvino in his book `Six Memos for the Next Millennium.'